1998
DOI: 10.1093/nar/26.14.3392
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion-dependent hydrolysis of RNA phosphodiester bonds within hairpin loops. A comparative kinetic study on chimeric ribo/2'-O-methylribo oligonucleotides

Abstract: Several chimeric ribo/2'- O -methylribo oligonucleotides were synthesized and their hydrolytic cleavage studied in the presence of Mg2+, Zn2+, Pb2+and the 1,4,9-triaza-cyclododecane chelate of Zn2+(Zn2+[12]aneN3) to evaluate the importance of RNA secondary structure as a factor determining the reactivity of phosphodiester bonds. In all the cases studied, a phosphodiester bond within a 4-7 nt loop was hydrolytically more stable than a similar bond within a linear single strand, but markedly less stable than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 62 publications
1
50
1
Order By: Relevance
“…As for the metal-ionpromoted cleavage, it has been suggested that bending of an RNA strand at an RNA bulge may create strong metal-ion coordination sites that are favorable for the catalysis [11]. In contrast, our previous results show that, in the presence of metal-ion catalysts, phosphodiester bonds within hairpin loops are clearly less reactive than those within linear oligonucleotides [9]. This difference was also attributed to the coordination of metal ions.…”
contrasting
confidence: 57%
See 3 more Smart Citations
“…As for the metal-ionpromoted cleavage, it has been suggested that bending of an RNA strand at an RNA bulge may create strong metal-ion coordination sites that are favorable for the catalysis [11]. In contrast, our previous results show that, in the presence of metal-ion catalysts, phosphodiester bonds within hairpin loops are clearly less reactive than those within linear oligonucleotides [9]. This difference was also attributed to the coordination of metal ions.…”
contrasting
confidence: 57%
“…As the most striking example, the phosphodiester bonds within RNA-RNA or RNA-DNA duplexes are relatively stable, their cleavage being very slow compared to the cleavage of phosphodiester bonds within single-stranded regions [6] ± [9]. This is true in both the absence and the presence of metal ion catalysts.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Conclusions, however, are not straightforward because different factors determine the sites of cleavage. Firstly, favorable backbone geometries for cleavage are more common in single-stranded and loop regions than in double-stranded helices [128,138]. On the other hand, strong relevant binding sites in a more rigid environment with an unfavorable geometry for inline attack might be missed.…”
Section: Metal Ion-induced Hydrolytic Cleavagementioning
confidence: 99%